Effectiveness of Glycyrrhiza uralensis extract on periodontal pathogens: a randomized controlled clinical trial - Kim, Yu-Rin; Nam, Seoul-Hee (BMC oral health, 2025)
Background This study aimed to evaluate the possibility of using a mouthwash containing Glycyrrhiza uralensis ( GU ) extract as an oral health improvement material to prevent periodontal disease using the clinical parameters and the changes in bacteria that cause periodontal disease. Methods A randomized, double-blind, controlled study was conducted on 60 patients who visited M dental clinic located in Busan, South Korea. The subjects were patients who agreed to complete the questionnaire, who were not included in the exclusion criteria, and had 16 or more remaining teeth. The patients were divided into two groups: the saline gargle solution group, which consisted of 30 patients; and the GU extract group, which consisted of 30 patients. Scaling was performed to ensure the same oral conditions between the two groups. After 1 week, 15 mL each of the gargle solution (saline and GU extract) was applied once a day for 30 s for 5 days. For the periodontal clinical parameters, O’Leary index, plaque index (PI), gingival index (GI), and periodontal-disease-related bacteria in subgingival plaques were examined (Baseline, After treatment, and After 5 Days). Results The use of the mouthwash containing GU extract significantly decreased the clinical values in all parameters of O’Leary index, PI, and GI ( p < 0.05). Also, after gargling using the mouthwash containing GU extract, the antibacterial effect on Gram-positive and Gram-negative bacteria that cause periodontal disease was confirmed to have excellent clinical effects in the inhibition, prevention, and treatment of periodontal disease. Conclusion The mouthwash containing GU extract can be beneficial in maintaining a healthy periodontal condition and oral hygiene through the reduction of O’Leary index, PI, GI, and periodontal-disease-related bacteria in the oral cavity, which has been proven in clinical applications.